The IAB Establishment Panel—methodological essentials and data quality - Peter Ellguth; Susanne Kohaut; Iris Möller (Journal for Labour Market Research, 2014)
The IAB Establishment Panel was launched to obtain information on the demand side of the labor market. This data meets two requirements: providing high quality data for the scientific aims and having an information system for policy makers and practitioners. As it started in 1993 a rich data set of 20 years establishment survey is available now. This article provides information about methodological issues of sample design and data sampling and changes that have taken place in recent years. We focus on quality issues, efforts to improve the survey and on some ongoing discussions about methodological adjustments of the survey mode.
Keywords: 330; IAB-Betriebspanel; Erhebungsmethode; Datengewinnung; Stichprobenverfahren; Hochrechnung; Datenqualität; Fragebogen; Datenverarbeitung; IAB-Linked-Employer-Employee-Datensatz; Datenzugang; Forschungsdatenzentrum; Befragung; Internet